Man's search for meaning - Viktor E Frankl (Boston,Massachusetts Beacon Press, 2006)
A prominent Viennese psychiatrist before the war, Viktor Frankl was uniquely able to observe the way that both he and others in Auschwitz coped (or didn't) with the experience. He noticed that it was the men who comforted others and who gave away their last piece of bread who survived the longest - and who offered proof that everything can be taken away from us except the ability to choose our attitude in any given set of circumstances. The sort of person the concentration camp prisoner became was the result of an inner decision and not of camp influences alone. Frankl came to believe man's deepest desire is to search for meaning and purpose. This outstanding work offers us all a way to transcend suffering and find significance in the art of living.
Keywords: Frankl, Viktor E. (Viktor Emil), 1905-1997.